Zingiber Officinale and Pure Honey in Overcoming The Invisibility Of Back Pain in Trimester III Pregnant Women - Dewi Nurlaela Sari; Yanyan Mulyani (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Low back pain is one of the discomfort felt by pregnant women, especially pregnancies that are in the third trimester. This study aims to determine the effect of Zingiber Officinale and pure honey in the handling of low back pain discomfort in Trimester III pregnant women. This type of research method is a quasi-experiment with one group pre-post test design approach. The sampling method used purposive sampling, namely as many as 51 respondents. The bivariate test used was the Wilxocon test with a paired t-test. The results showed that offering food and honey was effective in reducing the low back pain scale in pregnant women with a p-value (2-tailed) of 0.000 (p <0.05). In conclusion, it is found that there is an effect of offering female labor and pure honey in the management of low back pain in third-trimester pregnant women.